Bartın ve çevresi kırsal turizminin swot analizi - Emir, Gökhan; Emir, Gökhan (Mesleki Bilimler Dergisi, 2012)
Communities that commune with nature know a lot about nature and ecology. This knowledge both facilitates their lives and provides its sustainability. The people of Bartın, mainly rural population, live a life that communes with nature. Here, it is possible to see the effects of culture-environment interaction in every field of life. While the people of Bartın live in harmony with nature on the one hand, they form new alternative sources of income in the economic system forced by the outside world on the other hand. While doing this, they both benefit from the biologic and cultural values of the region and also consider the sustainability of these values. In this study, the aim is to determine the awareness of the people in Bartın region and the local businesses about rural tourism and to emphasize the necessity of a planned rural tourism structuring in Bartın. To put it another way, researching the feasibility of rural tourism in the region by specifying to what extent the people of the region are willing and ready to take part in rural tourism activities, is set as the focal point of this study.

Doğayla iç içe yaşam süren toplumlar doğa ve ekoloji hakkında çok şey bilirler. Bu bilgi hem onların yaşamını kolaylaştırır hem de sürdürülebilirliklerini sağlar. Kırsal nüfusun ağırlıkta olduğu Bartın insanı da doğayla iç içe bir yaşam sürdürür. Burada kültür-çevre ilişkisinin etkisini yaşamın her alanında görmek mümkündür. Bartın halkı bir yandan doğayla uyumlu bir yaşamı sürdürürken diğer yandan da dış dünyanın baskısını hissettirdiği ekonomik sistem içinde yeni alternatif geçim kaynakları da oluştururlar. Bunu yaparken hem yörenin biyolojik ve kültürel değerlerinden yararlanır hem de bu değerlerin devamlılığını gözetir. Bu çalışmada Bartın bölgesinde yaşayan halkın ve yerel işletmelerin kırsal turizmle ilgili farkındalığını tespit etmek ve Bartın’da planlı bir kırsal turizm yapılanma sürecinin gerekliliğinin belirtilmesi amaçlanmıştır. Diğer bir ifadeyle, bölge halkının kırsal turizm faaliyetleri içinde yer almaya ne düzeyde istekli ve hazır olduğunu belirleyerek kırsal turizmin bölgede uygulanabilirliğini araştırmak, çalışmanın odak noktası olarak belirlenmiştir.
Keywords: Sürdürülebilir turizm; Eko turizm; Black Sea Region; Sustainable tourism; Eco tourism; Batı Karadeniz Bölgesi; Kırsal turizm